Promotion of CO2 fracturing for CCUS—the technical gap between theory and practice - Hou, Lei; Luo, Jiangfeng; Gong, Peibin; Ji, Ya; Zhang, Lei (Frontiers in Energy Research, 2024)
CO2, used as an environmentally friendly fracturing fluid, has encountered a bottleneck in development in recent years. Despite great efforts in research work, limited progress has been made in field applications. In this study, an extensive literature review of research work and field cases was performed to summarize the technical issues and challenges of CO2 fracturing. The key issues of CO2 fracturing were analyzed to reveal the gap between fundamental research and field operations. The effects of CO2 properties on fracture creation and proppant transport were synthetically analyzed to extract new common research orientations, with the aim of improving the efficiency of CO2 injection. The hydraulic parameters of CO2 fracturing were compared with those of water-based fracturing fluids, which revealed a theory-practice gap. By studying the developing trends and successful experiences of conventional fluids, new strategies for CO2 fracturing were proposed. We identified that the major theory-practice gap in CO2 fracturing exists in pump rate and operation scale. Consequently, the friction reducer, effects of flow loss (due to leak-off) and distribution (within fracture networks), and shear viscosity of thickened CO2 are key factors in improving both fracture propagation and proppant transport. By increasing the scale of injected CO2, the CO2 fracturing technique can be enhanced, making it an essential option for carbon capture, utilization, and storage (CCUS) to reduce carbon emissions and mitigate climate change.